The returning dead: unconventional inhumations in Medieval Lithuania - Vėlius, Gintautas (Lietuvos istorijos studijos, 2010)
The paper analyses unconventional burials in Christian Lithuania in the 14th-17th centuries. The burials contain either headless or limbless bodies buried with face downwards or on their side; such inhumations are not to be attributed as occasional or entirely exceptive ones. These burials in substance do reflect the continuity of some certain pagan burial rituals and traditions.The great number of so-called unconventional inhumations in medieval Lithuania depict the permanent co-existence of both pagan post-existential concepts and rituals and the new Christian ones; such manner of beliefs is significant for a religiously syncretic society.Burial in unconventional position has been understood as an alleviation for the dead spirit on its way to the other world. Such rituals are also to be related with necrophobic beliefs as a way of avoiding the return of ineligible dead.The decollated individuals are to be related not with conventional burial traditions, but with desecrative exhumation, caused by the fear of the returning dead. According to Lithuanian folklore, such were untimely passed-away or greatly sinful persons. In Christian societies such posthumous decollations correlated with fight against vampires or with persons which caused pestilences.As the main reason of unquiet spirits, herewith of burials on the face or on a side of the body, should be determined an amiss, unexpected death. The great number of weapons in prone male burials presuppose attributing the latter as the graves of warriors fallen in battle.Unconventional burial traditions gradually vanished due to entrenchment of Christian concept of post-existence as well as due to burials in churchyards and sanctified cemeteries.
Keywords: -